Transformations in the Meaning of Unemployment - Smucker, Joseph (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
Over recent years the discourse of government policy-makers on the issue of unemployment has become transformed from a moral problem of social equity and the rights of citizens to an economic cost, necessary for a more efficient economy, useful in controlling inflation. This shift represents one outcome of a continual tension between social equity for the ostensibly free and equal citizen on one hand and preserving the "efficiency" of the economy on the other. The shift in the discussion of these cultural themes by policy makers has had an effect on the perspectives of the larger population.